EVALUATION OF ROOT PARALLELISM AFTER LEVELING IN CORRECTIVE ORTHODONTIC TREATMENT - Lapa, Ana Cristina Coelho Ferreira; Lima, André Lucas Rocha; Andrade, Rita de Cássia Dias Viana; de Freitas, Maria da Conceição Andrade; Motta, Rogério Heládio Lopes (Editora Impacto Científico, 2025)
This study aimed to evaluate the root parallelism in patients under orthodontic treatment by the Straight Wire technique through panoramic radiographs taken before and after the leveling phase, usually during the first nine months of treatment. The sample was composed of 40 initial and 40 post-leveling panoramic radiographs, where incisors, canines, premolars and first molars were measured. The Student t statistic test was used for the paired sample and the Wilcoxin statistic test was used for the not normal distribution data. The results presented a significant difference of the root inclination between the initial and the post- leveling panoramic radiographs in many teeth, except for the 11,13,31,32,35,42,45,46, that presented always higher values after the leveling phase, when significant statistical differences were observed (p<0,05). When the root inclinations of the “post leveling” group were compared to the ones found in previous studies, there were significant differences for most of the teeth, except for the 13, 23 and 24. As a conclusion, the values found in this study were higher for the inferior arch and lower for the superior arch. DOI: https://doi.org/10.56238/edimpacto2025.067-003